Use of irrigating substances of natural origin in Endodontics - Abraham-Millán, Yoneisy; Montano-Silva, Rosa María; Pupo-Martínez, Yaima (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The success of pulpo-radicular treatment involves the complete cleaning, disinfection and conformation of the canal system, which depends on the elimination of vital or necrotic pulp tissue, dentinal remnants and microorganisms. For this, the use of irrigating solutions with antimicrobial, chelating, solvent and hemostatic activity is essential. There are biopharmaceutical products created for this purpose. The objective was: to analyze the irrigating substances of natural origin used in the treatment of endodontic canals, considering the importance of this knowledge for stomatologists. The methods were used: documentary analysis, historical-logical analysis and analytical-synthetic. For the development of this research, 17 bibliographies were selected. Products of natural origin constitute an effective alternative for the irrigation of endodontic canals due to their antibacterial, antifungal, anti-inflammatory and analgesic properties; its main advantages are easy availability, profitability, low toxicity and the lack of microbial resistance reported to date.